A Chamber for Applying Pressure to Roots of Intact Plants - Gee, G. W. (1973)
A chamber was designed to apply up to 20 bars pressure to roots of intact plants. The unique features of this chamber are a split top arrangement to permit enclosing roots of intact plants within the chamber, a circulation coil to control temperature of rooting media, and a valve arrangement to permit changing solution without disturbing the plant. Changes in transpiration in response to changes in the pressure applied to roots of intact pepper plants illustrate one use of the equipment. Well watered plants at low light (0.05 langley/min) were observed to exude water from the leaf margins when 5 bars pressure was applied to the roots. When roots were cut off, a 1 bar pressure caused exudation. Plants with cooled roots or plants in dry soil did not exude water when as much as 6 bars pressure was applied. Transient response of transpiration rates to sudden application and release of pressure was observed in pepper and bean plants but not in rhododendron. The magnitude of this transient response was highly dependent upon light intensity and CO(2) concentration in the aerial environment.